Mexorchestia: a new genus of talitrid amphipod (Crustacea, Amphipoda, Talitridae) from the Gulf of Mexico and Caribbean Sea, with the description of a new species and two new subspecies - Wildish, David J.; Lecroy, Sara E. (Zootaxa, 2014)
Two species of supralittoral Tethorchestia were reported by Bousfield (1984) to occur on the shores of the Gulf of Mexico and closely adjacent waters: T. antillensis Bousfield, 1984 from Quintana Roo, Mexico and an undescribed species, Tethorchestia sp. B of Bousfield (1984), from Florida and the U.S. Gulf coast. In this paper, we rediagnose and illustrate the former taxon based on material from Goodland Bay, Florida, which represents a range extension for that species. We examined the latter taxon from many locations throughout the Gulf of Mexico using classical morphology, epidermal pigment pattern recognition and allometry, reinforced by molecular markers (mitochondrial cytochrome oxidase I, Radulovici 2012), determining that Tethorchestia sp. B represents a new genus and species, comprising two subspecies. The nominate subspecies, Mexorchestia carpenteri carpenteri n. gen., sp. and subsp., is described from Tiger Tail Beach, Florida, based on conventional morphological criteria and its distinctive epidermal pigment patterns. The Tiger Tail Beach ecotope of M. c. carpenteri n. gen., sp. and subsp. was distinct from that of other locations examined in Florida and was associated with epidermal pigment pattern polymorphism, absent at other locations. A second subspecies, distinguished by differences in size, number of articles in the flagellum of antenna 2, the number of marginal setae on oostegite 2 of the female and the number of distal dorsolateral robust setae on the telson, was found in samples from Belize and Mexico. This subspecies is described from material collected at Turneffe Island, Belize, as Mexorchestia carpenteri raduloviciae n. gen., sp. and subsp. Like M. c. carpenteri n. gen., sp. and subsp., this taxon is also associated with epidermal pigment pattern polymorphism. A key is provided for the three currently described species of Tethorchestia (two extant) and two new subspecies of Mexorchestia n.gen.